One-handed carrying among elderly and obese individuals: a systematic review to identify research gaps. Issue 10 (3rd October 2018) - Badawy, Mohamed; Schall, Mark C.; Sesek, Richard F.; Gallagher, Sean; Davis, Gerard A.; Capanoglu, M. Fehmi
Abstract: A systematic review of the literature regarding one-handed load carrying was conducted to identify research gaps for future load carrying studies. Twenty-six articles that may be relevant to elderly and obese people were included. Only two studies evaluated the effect of age as an independent variable during one-handed carrying. Obesity was not included as an independent variable in any of the articles. In general, the results suggested that one-handed carrying is more physically demanding than other methods of load carrying. In many cases, physiological responses to carrying a load in one hand were similar to carrying twice the load equally distributed between two hands. Some studies recommended a one-handed carrying weight limit of approximately 9–10 kg for men and 6–7 kg for women. However, more research on the effects of age and obesity during one-handed carrying is needed to determine if these results hold for elderly and obese people. Practitioner Summary: A systematic review of the scientific literature since 1966 regarding one-handed carrying that may pertain to elderly and/or obese people was performed. Few studies were identified that included aging and none included obesity as independent variables. Areas for future research are identified and discussed.